On some interesting marine decapod crustaceans (Alpheidae, Laomediidae, Strahlaxiidae) from Lombok, Indonesia - Anker, Arthur; Pratama, Idham Sumarto; Firdaus, Muhammad; Rahayu, Dwi Listyo (Zootaxa, 2015)
Several rare or uncommon, mostly infaunal decapod crustaceans are reported from intertidal and shallow subtidal habitats of Lombok, Indonesia. The alpheid shrimps Alpheus angustilineatus Nomura & Anker, 2005, Athanas shawnsmithi Anker, 2011, Jengalpheops rufus Anker & Dworschak, 2007, Salmoneus alpheophilus Anker & Marin, 2006, Salmoneus colinorum De Grave, 2004, and the laomediid mud-shrimp Naushonia carinata Dworschak, Marin & Anker, 2006, are reported for the first time since their original descriptions and represent new records for the marine fauna of Indonesia. The alpheid shrimps Alpheus macellarius Chace, 1988, Alpheus platyunguiculatus (Banner, 1953), Athanas japonicus Kubo, 1936, Athanas polymorphus Kemp, 1915, Leptalpheus denticulatus Anker & Marin, 2009, Richalpheus palmeri Anker & Jeng, 2006, Salmoneus gracilipes Miya, 1972, Salmoneus tricristatus Banner, 1959 and the laomediid mudshrimps Laomedia astacina De Haan, 1841 and Naushonia lactoalbida Berggren, 1992 are new records for Indonesian waters. The remaining alpheid shrimps, namely Alpheopsis yaldwyni Banner & Banner, 1973, Alpheus savuensis De Man, 1908, Automate anacanthopus De Man, 1910, Automate dolichognatha De Man, 1888, Salmoneus serratidigitus (Coutière, 1896), and the strahlaxiid mud-shrimp Neaxius glyptocercus (von Martens, 1869), all previously known from Indonesia, are recorded for the first time from Lombok. Colour photographs are provided for all species reported, some shown in colour for the first time.